EFFECTIVENESS OF SUGAMMADEX FOR REVERSAL OF NEUROMUSCULAR BLOCKADE IN OBSTETRIC AND GYNECOLOGIC SURGERY AT HAI PHONG OBSTETRICS AND GYNECOLOGY HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the efficacy of Sugammadex for the reversal of Rocuronium -induced neuromuscular blockade after obstetric and gynecologic surgery, and to assess its safety and potential adverse effects.Subjects and methods: A prospective descriptive study was conducted on 40 patients aged ≥ 18 years undergoing obstetric and gynecologic surgery, with Mallampati class I-II, who received general anesthesia with endotracheal intubation using Fentanyl, Propofol, and Rocuronium. Neuromuscular blockade was monitored using a tofscan device at the end of surgery, neuromuscular blockade was reversed with Sugammadex at a dose of 2 mg/kg upon reappearance of T2. The primary outcome measures included: time to recovery of TOF ratios > 0.5, > 0.7, and > 0.9; time to extubation; heart rate, blood pressure, and SpO2 at predefined time points following Sugammadex administration; total doses of Rocuronium, Sugammadex, and Propofol; incidence of bradycardia, tachycardia, and hypotension; and adverse events.Results: The mean duration of anesthesia was 68 ± 17.4 minutes, and the mean duration of surgery was 57 ± 15.2 minutes. The time from reappearance of T2 to TOF ratios >  0.5; >  0.7; and > 0.9 was 1.16 ± 0.33; 1.36 ± 0.50; and 1.59 ± 0.52 minutes, respectively. the mean time to extubation was 2.18 ± 0.38 minutes. Respiratory and hemodynamic parameters, as well as electrolyte levels, remained stable at all time points before and after Sugammadex administration. no adverse events related to Sugammadex were observed.Conclusions: Reversal of neuromuscular blockade with Sugammadex at a dose of 2 mg/kg following obstetric and gynecologic surgery provides effective recovery, with rapid reversal and a favorable safety profile.
Keywords: Sugammadex, obstetric and gynecologic surgery, Rocuronium.